TcMYB29a, an ABA-Responsive R2R3-MYB Transcriptional Factor, Upregulates Taxol Biosynthesis in Taxus chinensis - Cao, Xiaoying; Xu, Lingxia; Li, Ludan; Wan, Wen; Jiang, Jihong (Frontiers in Plant Science, 2022)
Paclitaxel (Taxol), a highly modified diterpene agent mainly obtained from Taxus species, is the most widely used anticancer drug. Abscisic acid (ABA) is a well-known stress hormone and plays important roles in secondary metabolism in plants, and it also can induce taxol accumulation in Taxus cell suspension cultures. However, the mechanism behind the regulation of taxol biosynthesis by ABA remains largely unknown. In previous research, a R2R3 MYB transcription factor (TF) TcMYB29a was observed to show a significant correlation with taxol biosynthesis, indicative of its potential role in taxol biosynthesis. Here, the TcMYB29a encoded by that gene was further characterized. Expression pattern analysis revealed that TcMYB29a was highly expressed in needles and roots. Over-expression of TcMYB29a in T. chinensis cell suspension cultures led to increased accumulation of taxol, and up-regulated expression of taxol-biosynthesis-related genes, including the taxadiene synthase (TS) gene, taxane 5a-hydroxylase (T5OH) gene, and 3'-N-debenzoyl-2'-deoxytaxol-N-benzoyltransferase (DBTNBT) gene as compared to the controls. Chromatin immunoprecipitation (ChIP) assays, yeast one-hybrid (Y1H) assays, electrophoretic mobility shift assays (EMSAs), and dual-luciferase reporter assays verified that TcMYB29a could bind and activate the promoter of TcT5OH. Promoter sequence analysis of TcMYB29a revealed that its promoter containing an AERB site from -313 to -319 was a crucial ABA-responsive element. Subsequently, ABA treatment assay showed that TcMYB29a was strongly up-regulated at 6 h after ABA pre-treatment. Furthermore, TcMYB29a was strongly suppressed at 3 h after methyl jasmonate (MeJA) treatment, and depressed to platform at 12 h. Taken together, these results reveal that TcMYB29a is an activator that improves taxol accumulation in T. chinensis cells through an ABA-medicated signaling pathway which is different from JA-medicated signaling pathways for taxol accumulation. These findings provide new insights into the potential regulatory roles of MYBs on taxol biosynthetic genes expression in Taxus.